DYNAMIC CHARACTERIZATION OF BALL BEARING IN TURBINE PROPELLER USING BUMP TEST METHOD - Monika Audiya Pratiwi; Muhammad Ikhsan; Rio Duzan Octavianto; Abdul Hamid; Subekti Subekti (SINERGI, 2021)
Bearing is an essential component in a mechanical rotating equipment system. It is no less important than lubrication to prevent wear is very important to consider in the mechanical maintenance system of rotating equipment. Bearing wear is one of the problems in wind turbines that will increase maintenance costs, shorten the wind turbines' lifespan, and cause the component or overall damage to the wind turbine. The latest technology has provided instruments for analyzing the damage of elements in a bearing according to the caused vibrations. Therefore, this study was performed on Ball Bearing Turbine Propeller to identify the dynamic characteristics of Ball Bearing with and without lubrication. The test was carried out using the Bump Test method applied in three measured parts: X, Y, and Z axes. The measuring instrument which was used was Fast Fourier Transform (FFT) Analyzer (Ono Sokki) and the data were analyzed using MATLAB. It was identified that the application of oil could reduce the amplitude and decrease the frequency. Personal frequency appearing more than once indicates the existence of global vibration modes. The frequency which only appears once in the measurement spot indicates local vibration modes. The highest frequency both after and before the application of oil was found in the Y-axis.